Correlation between Serum Albumin Level and Degree of Esophageal Varices in Patients with Liver Cirrhosis - Dewa Gde Agung Budiyasa; Yuna Ariawan; I Ketut Mariadi; I Dewa Nyoman Wibawa; Nyoman Purwadi; I Gusti Agung Suryadarma (The Indonesian Society for Digestive Endoscopy, 2011)
Background: It has not been clear about how often the patient should have esophago- gastroduodenoscopy (EGD) screening for esophageal varices (EV) detection and there is only some data that demonstrates the correlation between the degree of EV and non-endoscopic variables. It is assumed that the presence of EV detected though examination of serum albumin level may trim down the unnecessary endoscopy. This study was aimed to recognize the correlation between albumin level and the degree of EV in patients with liver cirrhosis. Method: A retrospective analysis was performed for 61 patients with liver cirrhosis who had EGD at Sanglah hospital between January and December 2008. Spearman test was used to analyze the correlation between albumin level and the degree of EV. Results: There were 61 patients of 45 (73.8%) male and 16 (26.2%) female. The range age of patients was 13–77 years (average 49.98 ± 1.62 years). Serum albumin level ranged between 1.10-3.60 mg/dL, the average value was 2.21 ± 0.451 mg/dL. We also found 8 (13.1%) patients without EV, 14 (23.0%) patients with EV grade I, 21 (34.4%) patients with grade II and 18 (29.5%) patients with grade III. A negative correlation was found between serum albumin level and the degree of EV (r = - 0.587; p = 0.000, p 0.01). Conclusion: Serum albumin level can predict the presence and the degree of EV in patients with liver cirrhosis. Keywords: albumin, degree of EV, liver cirrhosis